Forchlorfenuron Alters Mammalian Septin Assembly, Organization, and Dynamics - Hu, Qicong (American Society for Biochemistry and Molecular Biology, 2008)
Septins are filamentous GTPases that associate with cell membranes and the cytoskeleton and play essential roles in cell division and cellular morphogenesis. Septins are implicated in many human diseases including cancer and neuropathies. Small molecules that reversibly perturb septin organization and function would be valuable tools for dissecting septin functions and could be used for therapeutic treatment of septin-related diseases. Forchlorfenuron (FCF) is a plant cytokinin previously shown to disrupt septin localization in budding yeast. However, it is unknown whether FCF directly targets septins and whether it affects septin organization and functions in mammalian cells. Here, we show that FCF alters septin assembly in vitro without affecting either actin or tubulin polymerization. In live mammalian cells, FCF dampens septin dynamics and induces the assembly of abnormally large septin structures. FCF has a low level of cytotoxicity, and these effects are reversed upon FCF washout. Significantly, FCF treatment induces mitotic and cell migration defects that phenocopy the effects of septin depletion by small interfering RNA. We conclude that FCF is a promising tool to study mammalian septin organization and functions.